Simulating Correlations of Structured Spontaneously Down-Converted Photon Pairs - Trajtenberg-Mills, Sivan; Karnieli, Aviv; Voloch-Bloch, Noa; Megidish, Eli; Eisenberg, Hagai S.; Arie, Ady (Laser & Photonics Reviews, 2020)
Introducing structure into photon pair generation via spontaneous parametric down-conversion (SPDC) is shown to be useful for controlling the output state and exploiting new degrees of freedom for quantum technologies. This paper presents a new method for simulating first- and second-order correlations of the down-converted photons in the presence of structured pump beams and shaped nonlinear photonic crystals. This method is nonperturbative, and thus accounts for high-order effects, and can be made very efficient using parallel computing. Experimental results of photodetection and coincidence rates in complex spatial configurations are recovered quantitatively by this method. These include SPDC in 2D nonlinear photonic crystals, as well as with structured light beams such as Laguerre Gaussian and Hermite Gaussian beams. This simulation method reveals conservation rules for the down-converted signal and idler beams that depend on the nonlinear crystal modulation pattern and the pump shape. This scheme can facilitate the design of nonlinear crystals and pumping conditions for generating non-classical light with pre-defined properties.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/lpor.201900321
Keywords: NONLINEAR optics; Quantum optics; spontaneous parametric down-conversion; structured light; vortex beams